KENDALA TERJADINYA PERMASALAHAN DALAM IMPLEMENTASI UNDANG-UNDANG PERLINDUNGAN ANAK - Ariyanti, Alya; Hunainah (Taruna Law: Journal of Law and Syariah, 2025)
The implementation of the Child Protection Law (UUPA) in Indonesia faces a number of significant obstacles that hinder the achievement of the goal of protecting children's rights effectively. This study evaluates the main challenges that arise in the implementation of the UUPA. These obstacles include limitations in institutional resources and capacity (limited budget, lack of competent workers, and inadequate infrastructure); lack of coordination and synergy between institutions (overlapping authorities, weak referral mechanisms, and unintegrated data); variations in understanding and enforcement of the law (lack of understanding among officials and the community, and inconsistent enforcement); the existence of social stigma, patriarchal culture, and challenges in the digital world; and children's participation that has not reached optimal levels. This article concludes that the complexity of the issue requires comprehensive cooperation from all parties involved, including increasing the budget, strengthening capacity, adjusting institutions, disseminating broad laws, and adapting to new methods of crime. By addressing these challenges, it is hoped that the UUPA can operate more effectively in creating a safe environment and supporting the growth and development of children in Indonesia.